The Drosophila hairy protein acts in both segmentation and bristle patterning and shows homology to N-myc. - Rushlow, C.A.; Hogan, A.; Pinchin, S.M.; Howe, K.M.; Lardelli, M.; Ish-Horowicz, D. (The EMBO Journal, 1989)
The Drosophila segmentation gene, hairy (h), acts to regulate embryonic segmentation and bristle pattern. We present the DNA sequence of the h gene and of h cDNAs, thereby deducing the organization of the h transcripts. The h gene encodes a 337 amino acid protein that acts in both embryonic segmentation and adult bristle patterning. The h protein includes a domain that shows extensive similarity to a domain of the proto-oncogene N-myc that may be involved in DNA binding and/or protein dimerization. We discuss mechanisms of h action as a transcriptional regulator.